Analysis of replicative intermediates of adeno-associated virus through hirt extraction and southern blotting. - Bardelli, M; Zarate-Perez, F; Agundez, L; Jolinon, N; Michael Linden, R; Escalante, C; Henckaerts, E (Bio-Protocol, 2017)
Adeno-associated virus (AAV) is a small single-stranded DNA virus that requires the presence of a helper virus, such as adenovirus or herpes virus, to efficiently replicate its genome. AAV DNA is replicated by a rolling-hairpin mechanism (Ward, 2006), and during replication several DNA intermediates can be detected. This detailed protocol describes how to analyze the AAV DNA intermediates formed during AAV replication using a modified Hirt extract (Hirt, 1967) procedure and Southern blotting (Southern, 1975).